2013
DOI: 10.15241/rla.3.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Role Diffusion in School Counseling

Abstract: Chronic illness and disability (CID) impact more than 35 million Americans, often interfering with their everyday life (Livneh & Antonak, 1997). The condition is typically accompanied by a prolonged course of treatment, an often uncertain prognosis, constant and intense psychosocial stress, increasing interference with the performance of daily activities and life roles, and conflict with family and friends (Livneh & Antonak, 1997). Approximately 11% of undergraduate students reported having a disability in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
0
22
0
3
Order By: Relevance
“…Tyrimo rezultatai rodo, kad dažnai mokinių konsultavimo funkcijos yra priskiriamos įvairių sričių profesionalams: Lietuvoje šias funkcijas dažniausiai atlieka psichologai, Airijoje -mokyklų konsultantai, Italijoje -mokytojai. Jeigu rengiant psichologus ar socialinius darbuotojus studijų programose galima tikėtis rasti karjeros konsultavimo discipliną, tai realioje mokyklų praktikoje galima sutikti konsultavimo profesionalų, turinčių savo nuosavą pasirengimo konsultuoti kvalifikaciją (Cedefop, 2009;Astramovich et al, 2013;Evans, Payne, 2008;Agresta, 2004).…”
Section: Rezultatų Aptarimasunclassified
See 2 more Smart Citations
“…Tyrimo rezultatai rodo, kad dažnai mokinių konsultavimo funkcijos yra priskiriamos įvairių sričių profesionalams: Lietuvoje šias funkcijas dažniausiai atlieka psichologai, Airijoje -mokyklų konsultantai, Italijoje -mokytojai. Jeigu rengiant psichologus ar socialinius darbuotojus studijų programose galima tikėtis rasti karjeros konsultavimo discipliną, tai realioje mokyklų praktikoje galima sutikti konsultavimo profesionalų, turinčių savo nuosavą pasirengimo konsultuoti kvalifikaciją (Cedefop, 2009;Astramovich et al, 2013;Evans, Payne, 2008;Agresta, 2004).…”
Section: Rezultatų Aptarimasunclassified
“…Konsultantų vaidmenų neaiškumas, dviprasmiškumas, sumaištis yra analizuojama jau daugiau negu pusę amžiaus (Astramovich et al, 2013;Gysbers and Stanley, 2014;Lambie, Williamson, 2004). Autorių teigimu, konsultantų mokykloje vaidmenų neapibrėžtumas siejamas su neteisingu konsultantų darbo supratimu ir mokyklos vadovų priskiriamomis funkcijomis, siekiant efektyvaus mokyklos valdymo.…”
unclassified
See 1 more Smart Citation
“…School counselors receive conflicting obligations and messages from counselor educators, school administrators and other stakeholders. However, research has found that among usual school counselor duties, direct counseling services are the most unique role of school counselors (Astramovich, Hoskins, Gutierrez, & Bartlett, 2014). Counseling services are often underutilized.…”
Section: School Counselor Professional Identitymentioning
confidence: 99%
“…Another concern is that the instrument was developed in alignment with the ASCA National Model (2005,2012). Although this model is considered the professional standard for school counseling, the ASCA National Model is flawed, criticized for lacking a supervision element (Murphy & Kaffenberger, 2007) and for its diminishing focus on counseling (Astramovich, Hoskins, Gutierrez, & Bartlett, 2013). The ASCA National Model is not the only school counseling model that exists.…”
Section: Limitationsmentioning
confidence: 99%